Exploring the efficacy of different electric field models in driving a model of the plasmasphere. Issue 6 (20th June 2014) - Ridley, A. J.; Dodger, A. M.; Liemohn, M. W.
Abstract: The dynamics of the plasmasphere are strongly controlled by the inner magnetospheric electric field. In order to capture realistically the erosion of the nightside plasmapause and the formation of the drainage plume in a model of the plasmasphere, the electric field must be accurate. This study investigates how well five different electric field models drive the Dynamic Global Core Plasma Model during eight storm periods. The five electric field models are the Volland‐Stern analytic formula with Maynard‐Chen Kp dependence, two versions of the Weimer statistical models (96 and 05), and two versions of the Assimilative Mapping of Ionospheric Electrodynamics (AMIE) technique using magnetometer and DMSP satellite data. Manually extracted plasmapause locations from images taken by the EUV instrument on the Imager for Magnetopause‐to‐Aurora Global Exploration (IMAGE) satellite, as described by Goldstein et al. (2005), were compared to the simulation results throughout the main phase of the eight events. Three methods of calculating the plasmapause were employed to determine the best fit to EUV data, using the maximum gradient, a constant density contour (fit method), and the location in which the modeled density fell significantly below the specified saturation density for the given radial position (saturation method). It was found that the simulations driven by the Weimer (1996) model produced the best fit overall and that the fit and saturation methods worked best for matching the model results to the observations. Key Points: The Weimer [1996] model works quite well for driving the plasmasphere A saturation technique for determining the plasmapause location in introduced Plasmapause determined by IMAGE may not be the steepest gradient in density